An evaluation of rural–urban disparities in treatment outcomes for obstructive sleep apnoea: study protocol for a prospective cohort study. Issue 4 (5th October 2020) - Corrigan, Jennifer; Ogah, Imhokhai; Ip-Buting, Ada; Sharpe, Heather; Laratta, Cheryl R.; Peller, Peter; Tsai, Willis H.; Pendharkar, Sachin R.
Background: Obstructive sleep apnoea (OSA) is a common and treatable chronic condition that is associated with significant morbidity and economic cost. Geography is increasingly being recognised as a barrier to diagnosis and treatment of many chronic diseases; however, no study to date has investigated the impact of place of residence on health outcomes in OSA. Objective: The purpose of this study is to determine whether treatment outcomes for patients initiating continuous positive airway pressure (CPAP) for OSA differ between those who live in urban versus rural settings. Methods: A prospective cohort design will be used. Participants will be recruited through community-based CPAP providers and assigned to either the rural or urban cohort based on residential postal code. The primary outcome will be the difference in nightly hours of CPAP use between the two groups, measured 3 months after initiation of therapy. Secondary outcomes will include symptoms, quality of life, patient satisfaction and patient-borne costs. Anticipated results: This study will determine whether there are differences in CPAP adherence or patient-reported outcomes between rural and urban patients with OSA. These results will highlight potential challenges with providing OSA care in rural populations and may inform health interventions to reduce urban–rural inequities. Do obstructive sleep apnoea treatment outcomes differ between rural and urban populations? Engagement of community providers enables a novel approach to real-world evaluation. #sleep @ERSpublications https://bit.ly/3cGps6X